KOMPOSISI “CLIMENTALIA” - AGUSTINUS WELLY HENDRATMOKO (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2018)
This article discusses the process of ‘karawitan’ creation with the title ‘Climentalia’ derived from a combination of words or terms, ‘climen’ and ‘instrumentalia’. ‘Climentalia’ is a composition of ‘karawitan’ with ‘climen’ format, small or incomplete (cokѐkan). This composition is made by combining idioms and different mediums of ‘karawitan’ conventionally in an attempt to discover something new. The basic concept of this composition is the development of musical themes with the initial stimulus motifs of ‘gendѐr’ playing that are processed with various ornamentation of musical elements and vocals. This work is an exploration of the mix between the nuances of jazz music, idiom nuances of ethnic Chinese and the exploration of musical elements that exist in the Javanese musical tradition.